PERAN LIFE CYCLE STAGE DALAM MEMODERASI HUBUNGAN ANTARA INTELLECTUAL CAPITAL DISCLOSURE DAN NILAI PERUSAHAAN - Arif Pujianto; Wiwik Utami; Istianingsih Sastrodiharjo (Department of Accounting-Faculty of Economic and Business (FEB), 2016)
The purpose of this study was to identify interactive effect of the life cycle stage on the relationship of intellectual capital disclosure and corporate value. Components of intellectual capital disclosure is human capital disclosure, structure capital disclosure and customer capital disclosure. Life cycle stage was interest to be reviewed as there are differences finding on previous research.The population were manufacturing companies listed on the Indonesia Stock Exchange during the period 2009 – 2011.Based on purposive sampling there were 70 companies was selected. The multiple regression method was used to analyze the interactive effect. The results of this study demonstrate that Life cycle stages not moderates the relationship of intellectual capital disclosure and corporate value. This finding has an important role in the management accounting literatureDOI: 10.15408/akt.v9i1.3588